3D Printing: Rational Design of Ultrasensitive Pressure Sensors by Tailoring Microscopic Features (Adv. Mater. Interfaces 18/2018). Issue 18 (21st September 2018) - Peng, Shuhua; Blanloeuil, Philippe; Wu, Shuying; Wang, Chun H.
Abstract : Ultrasensitive resistive pressure sensors are developed by using an additive manufacturing technique (3D printing) to create contacting surfaces with different microstructure features. These new sensors' performance is highly tunable by adjusting the surface topographic features. More details can be found in article number1800403 by Shuhua Peng, Chun H. Wang, and co‐workers.